The Role of Good governance in Transmitting the Influence of New public Management and Leadership in Public Servants’ Performance - Bambang Istianto; Albertus Wahyurudhanto (Universitas Muhammadiyah Yogyakarta, 2022)
Grounded in the relationship-based view, the current study aims to examine the impact of new public management and leadership on the performance of civil servants via an underlying mechanism of good governance practices. Data has been collected from the leaders and officials of civil services in Jakarta, Indonesia, via purposive sampling techniques. Data were analyzed using structural equation modeling in SmartPLS 3.0. Findings revealed the significant influence of the new public management in strengthening the perceptions of good governance among the civil servants, resulting in their higher performances. Likewise, results also revealed the significant influence of public leadership in building positive perceptions of good governance, leading to the increased productivity of the civil servants. The current study is a valuable addition to the existing body of literature by uniquely exploring the impact of new public management and leadership together in enhancing perceptions of good governance among the civil servants utilizing the relationship-based view. Moreover, theoretical and practical implications, along with the future research directions, are discussed in detail.